Robustly embodied imagination and the limits of perspective-taking. - Clavel Vázquez, María Jimena; Clavel-Vázquez, Adriana (Philosophical Studies, 2023)
Experiential imagination consists in an imaginative projection that aims at simulating the experiences one would undergo in different circumstances. It has been traditionally thought to play a role in how we build our lives, engage with other agents, and appreciate art. Although some philosophers have recently expressed doubts over the capacity of experiential imagination to offer insight into the perspective of someone other than our present-selves, experiential imagination remains a much sought-after tool. This paper substantiates pessimism about the epistemological value of these uses of experiential imagination by developing an embodied approach. Our thesis is that experiential imagination is robustly embodied because the sociohistorically situated body makes an irreducible contribution to the imaginative project, and that, as such, it is constrained by who we are as concrete agents. We argue that experiential imagination is an embodied, virtual exploration of imagined scenarios that depends on our situated history of sensorimotor and affective interactions. We conclude that experiential imagination is much more limited than commonly acknowledged, as it can hardly be divorced from who we are and where we have been.